Analisis Pengetahuan, Dukungan Keluarga terhadap Praktik Kader Posbindu PTM dalam Melakukan Kie Sadari di Wilayah Kerja Puskesmas Kecamatan Bogor Bara - Anggun Nur Aisah; Agustin Kusumayati (Jurnal Health Sains, 2021)
One of the health problems in Indonesia is cancer. Among all types of cancer, cervical cancer and breast cancer are the most common types of cancer suffered by women in the world. The purpose of this study is to find out the relationship of knowledge, family support with the practice of KIE SADAR in the working area of west Bogor sub-district health center. This research is descriptive research with a quantitative approach and cross sectional research design that aims to find out the picture of knowledge and support of the family of PTM posbindu cadres in the working area of west Bogor sub-district health center. Research subjects as many as 92 ptm posbindu cadres divided into 5 working areas of West Bogor sub-district health center. The results of the chi square test obtained a value of p = 0.008 then it can be concluded that there is a significant relationship between knowledge and the practice of KIE SADAR obtained value OR = 3.46 means that good knowledge cadres have the opportunity to practice KIE SADAR 3.4 times compared to low knowledge cadres. There is a significant relationship between family support and KIE SADAR Practice with a value of p = 0.017 with an OR value = 4,248 means that cadres who get family support have the opportunity to do KIE SADAR Practice 4.2 times compared to cadres not getting family support.